Empowerment management of The Asik Literacy Program based on Appreciative Inquiry to improve the quality of learning - Rahmi Rahmi; Madhakomala R. (LPPM STKIP Kusuma Negara, 2026)
Improving the quality of education is not only based on human resource capabilities, but also strategic management approaches in various aspects of school management. One example in planning the empowerment of Asik literacy program based on appreciative inquiry which is used to maximize student potential. The target of partispan in this research starts from students, teachers and parents in Bekasi city state high school. The study was designed as a study in retrospective subjects with comparison of pre-post self-reports using retrospective memories. Findings from evaluation and participant feedback stated that the Asik literacy program based on appreciative inquiry was proven to create an effective and flexible learning environment so that this approach supports improving the quality of more comprehensive learning. The findings of this study help to understand the psychology of students in the absorption of effective learning by integrating social and moral support from human relations approach in education.